Traditions that we encounter now recorded neatly by mukharrij its individual, but when we examine the authenticity of a tradition that exists in the book, there are issues that are very important to note that the process of transformation of the Prophet to the Companions, or of the Companions to the transmitters thereunder before the tradition was recorded, whether in his narration with lafaz, or with meaning. Although the majority of scholars allow the transmission of bi al-ma'na with strict re - Ade Jamarudin (UIN SUSKA RIAU, 2015)
Qur’an repreatedly encourages thorough and human concern with various way, so that people use their minds. Sense is the spiritual potential of the human being who has ability to theoretically understand cosmic reality that surrounds and practically change and inffluence. Reason is the ability of human beings in the form capability intelligence that can be sized, controlled and regulator of actions both practically and theoretically. In the Qur’an mind gets clear enough portion, resident as a means of thinking about and understanding the absolute truth that is brought about by the profhet treatise